Why do entrepreneurs refuse venture capital?. Issue 6 (3rd July 2019) - Croce, Annalisa; Grilli, Luca; Murtinu, Samuele
ABSTRACT: Despite the evidence on the positive effect of venture capital (VC) on portfolio firm performance, such evidence badly pulls up alongside the non-negligible number of entrepreneurial firms that choose to refuse VC. This is the first study that investigates the determinants behind the missed realizations of VC investor-investee dyads by focusing on the Italian VC market. We theorize and empirically document that entrepreneurs' human capital background and venture-specific characteristics influence the decision to accept or refuse VC. Specifically, our findings show that technically literate founders decrease the likelihood to refuse VC while family linkages in the ownership structure increase the likelihood to refuse VC.